TRANSFORMASI MANAJEMEN BISNIS DI ERA IOT: ANALISIS SWOT DAN BMC UNTUK TANTANGAN TEKNOLOGI - Aldi Bagus Prasetya, Ahmad; Murni Puspita, Safriya; Amrozi, Yusuf (Jurnal Intelek Insan Cendikia, 2024)
The implementation of the Internet of Things (IoT) in business management offers significant opportunities to enhance operational efficiency, enrich customer experience, and support data-driven decision-making. IoT enables companies to collect and analyze real-time data, increasing their ability to respond to market changes more quickly and accurately. However, the adoption of this technology also presents challenges such as high initial costs, security issues, and the need for competent digital leadership. To develop the right strategies, companies can use strategic analysis tools like SWOT analysis and Business Model Canvas (BMC). Through SWOT analysis, companies can identify the strengths, weaknesses, opportunities, and threats in implementing IoT, while BMC allows companies to design adaptive business models focused on customer needs. By developing customer-centric solutions, investing in digital leadership, and prioritizing security, companies can fully leverage IoT and create sustainable competitive advantages.